Effectiveness Test of Parasitization by Parasitoid Tricogramma japonicum in Controlling White Rice Stem Borer (Scirphopaga innotata) - Susilawati Astrodjojo; Suratman Sudjud; Sri Soenarsih DAS (Food, Agriculture and Natural Resources - NETWORKS, 2021)
Rice is an essential food crop besides corn and soybeans. The need for rice each year increases along with population growth. One of the pests affecting rice is the white rice stem borer. The present research aimed to test the effectiveness and to examine the interaction between plant age and the number of Tricogramma japonicum parasitoid. The research was carried out at the Agrotechnology Laboratory of the Faculty of Agriculture, Khairun University, Ternate, and the rice fields of Bumi Restu village SP I, East Wasile district. The research design operative was a randomized block design where factor A (A1 = 21 DAS, A2 = 42 DAS, A3 = 56 DAS) was the age of the plant, and factor B (B0 = 0, B1 = 50, B2 = 100, B3 = 150) was the number of eggs of Corcyra cephalonica. Biological control using different amounts of Trichogramma japonicum parasitoid led to different interactions and results for each tested parameter. For the number of egg groups, there was no interaction with plant age, but the treatments which were found effective in suppressing stem borer populations were B2 and B3 (100 and 150). The most effective pias as indicated by damage intensity parameter was B3 (150), which was applied to plants aged 21 DAP. Furthermore, for plant height, different number of parasitoids poses significantly effective results. Percentage unhulled grain of pias B3 (150) causes insignificant damage. For production there is no interaction with plant age, but pias B2 (100) shows high yield. The conclusion is that pias B3 (150) applied to 21 days of plants is very effective in controlling white rice stem borer.